The effects of problem-based learning on students' achievements in primary school chemistry - Zejnilagić-Hajrić, Meliha; Šabeta, Alma; Nuić, Ines (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2015)
Specific applications of cognitive and constructivist theories in problem-based learning (PBL) include connecting prior knowledge and skills with new information. This prominent instructional method is widely accepted in higher education around the world, but it also shows good results when applied in primary education of various disciplines. This paper presents effects of PBL application in 8th grade primary school chemistry when learning about chemical compounds, using questionnaires and tests of knowledge in pretest-posttest study with control (CG) and experimental (EG) groups. Students in CG were taught in usual way with teacher-centered approach, while in EG the PBL materials designed for the purpose of this study were applied. Results showed (1) significant improvement of students’ achievements in EG, (2) these students are not used to this teaching method so they encountered certain difficulties, (3) overall interest and engagement in chemistry lessons has increased.